Sublines of Omicron Genovariant of SARS-CoV-2 Virus as Potential Dominant Agents of New Rises of COVID-19 Morbidity in Russia - T. E. Sizikova; N. V. Karulina; A. A. Petrov; V. N. Lebedev; S. V. Borisevich (Вестник войск РХБ защиты, 2024)
The analysis of existing information about invasion of COVID-19 in Russia shows that that one of leading reason of  existing of new rises of covid-19 morbidity is distribution of new genovariants of SARS-CoV-2 virus. The omicron  genovariant of SARS-CoV-2 virus was a dominant agent of fifth and subsequent rises of COVID-19 morbidity in  Russia. The aim of this work – the estimation of sublines of omicron genovariant of SARS-CoV-2 virus as potential  dominant agents of new rises of COVID-19 morbidity in Russia. The source base of the study. Data published in  Russian and English-language scientific publications available via the Internet (RSCI, PubMed, Google Scholar). The  research method is analytical. Results. The basic properties of omicron genovariant of SARS-CoV-2 virus, epidemical  characteristics of the rises of COVID-19 morbidity in Russia, caused by new sublines of omicron variant, estimation  ofsublines of omicron genovariant as potential dominant agent of new rises of COVID-19 morbidity in Russia are  viewed. It is shown that basic direction of SARS-CoV-2 virus evolution is existing of sublines of omicron genovariant,  which are characterized by increased transmissivity but with less severity of the disease caused compared to previously  circulated variants of COVID-19agent. The main distinguishing feature of the new subvariants («Kraken», «Czerber»,  «Centaur», «Arktur», «Pirola») are multiple amino acid exchanges in structural glycoprotein S. The maximum level  of variability of this structural protein compared to the original variant of SARS-CoV-2 virus is marked for Pirola  subvariant. Onle Kraken subvariant was dominant agent of rise of COVID-19 morbidity in Russia. Conclusion. New  rises of COVID-19 morbidity in Russia will not be connected with existing of new subvariants of omicron genovariant,  but only with season factor.